An Economic Model of Brazil's Ethanol-Sugar Markets and Impacts of Fuel Policies - de Gorter, Harry; Drabik, Dusan; Kliauga, Erika M.; Timilsina, Govinda R. (2013)
The lack of growth in the Brazilian sugarcane-ethanol complex since the 2008 financial crisis has been blamed on policies: lower mandate, holding gasoline prices below world levels, high fuel taxes, and inadequate fuel tax exemptions for ethanol. This paper develops an empirical model of the Brazilian fuel-ethanol-sugar complex to analyze the impacts of these policies. Unlike biofuel mandates and tax exemptions elsewhere, Brazil's fuel-ethanol-sugar markets and fuel policies are unique such that each policy, in theory, has an ambiguous impact on the market price of ethanol and hence on sugarcane and sugar prices. The results indicate two policies that seemingly help the ethanol industry do otherwise in reality: low gasoline taxes and high anhydrous tax exemptions lower ethanol prices. But higher mandates, hydrous ethanol tax exemptions, and gasoline prices had the expected impact of increasing ethanol and sugar prices. Eliminating Brazilian ethanol tax exemptions and mandates reduces ethanol prices by 21 percent. Observed changes in prices are explained by outward shifts in fuel transportation and sugar export demand curves, and bad weather reducing sugarcane supply.